Comparison of crystal structure and DFT calculations of triferrocenyl trithiophosphite’s conformance - Shekurov, Ruslan P.; Khrizanforov, Mikhail N.; Bezkishko, Ilya A.; Gerasimova, Tatiana P.; Zagidullin, Almaz A.; Islamov, Daut R.; Miluykov, Vasili A. (Beilstein Journal of Organic Chemistry, 2022)
A triferrocenyl trithiophosphite was studied by X-ray single-crystal diffraction. Triferrocenyl trithiophosphite has nine axes of internal rotation: three P–S bonds, three C–S bonds and three Fe–cyclopentadienyl axes. Rotation around the P–S bonds results in a totally asymmetric structure with three ferrocenylthio groups exhibiting different orientations towards the phosphorus lone electron pair (LEP). A comparison of DFT calculations and X-ray diffraction data is presented, herein we show which conformations are preferred for a given ligand.
Keywords: DFT calculations; multi-ferrocenyl compounds; phosphorus thioesters; trithiophosphite; X-ray